Rural Socio-Economic Transformation: Agrarian, Ecology, Communication and Community, Development Perspectives : Proceedings of the International Confernece on Rural Socio-Economic Transformation: Agrarian, Ecology, Communication and Community Development Perspectives (RUSET 2018), November 14-15, 2018, Bogor, West Java, Indonesia /: Proceedings of the International Confernece on Rural Socio-Economic Transformation: Agrarian, Ecology, Communication and Community Development Perspectives (RUSET 2018), November 14-15, 2018, Bogor, West Java, Indonesia. (2019) - Unknown
No abstract available